Screening for Cognitive Function in Complete Immobility Using Brain–Machine Interfaces: A Proof of Principle Study - Lulé, Dorothée; Hörner, Katharina; Vazquez, Cynthia; Aho-Özhan, Helena; Keller, Jürgen; Gorges, Martin; Uttner, Ingo; Ludolph, Albert C. (Frontiers in Neuroscience, 2018)
Background: In many neurological conditions, there's a combination of decline in physical function and cognitive abilities. For far advanced stages of physical disability where speaking and hand motor abilities are severely impaired, there is a lack of standardized approach to screen for cognitive profile. Methods: N=40 healthy subjects were included in the study. For proof of principle, N=6 ALS patients were additionally measured. For cognitive screening, we used the Edinburgh cognitive and behavioural ALS screen (ECAS) in the standard paper and pencil version. Additionally, we adapted the ECAS to a brain machine interface (BMI) control module to screen for cognition in severely advanced patients. Results: There was a high congruency between BMI version and the paper-and pencil version of the ECAS. Sensitivity and specificity of the ECAS-BMI was mostly high whereas stress and weariness for the patient was low. Discussion / Conclusion: We hereby present evidence that adaptation of a standardised neuropsychological test for BMI control is feasible. BMI driven neuropsychological test provide congruent results compared to standardized tests with a good specifity and sensitivy but low patient load.